Peran Dukungan Sosial Pengasuh dan Religiusitas terhadap Hardiness pada Remaja di Panti Asuhan - Andrianto Andrianto; Faridah Ainur Rohmah (Universitas Ahmad Dahlan, 2021)
Role Caregiver Social Support andReligiosity with Hardiness among Adolescents in Orphanages.Adolescents are burdened by problems of friendship, school and family pressures. This makes adolescents become stressed or depressed so that they need strong personality attributes including hardiness.This study aims to examine the relationship between caregiver social support and religiosity with hardiness in adolescents in orphanages. This study uses a quantitative method with a scale as a tool for data collection. The number of subjects in this study were 64 teenagers who lived at the Muhammadiyah Putra Orphanage in Yogyakarta. There are three scales used, namely the hardiness scale, caregiver social support and religiosity. The data analysis technique used is multiple linear analysis with the help of SPSS 16.0 for windows. The results of the data analysis showed a very significant relationship between caregiver social support and religiosity with hardiness. The higher the caregiver's social support, the higher the hardiness and vice versa. The higher the religiosity, the higher the hardiness and vice versa. Based on the results of the study, it was concluded that there was a very significant relationship between social support from caregivers and religiosity with hardiness in adolescents in orphanages.Â